2016
DOI: 10.3390/ijerph13121183
|View full text |Cite
|
Sign up to set email alerts
|

Association between Family and Friend Smoking Status and Adolescent Smoking Behavior and E-Cigarette Use in Korea

Abstract: Smoking is harmful to the health of adolescents because their bodies are still growing. The aim of this study was to analyze the association between the smoking status of Korean adolescents’ parents and friends and their own smoking behavior. The study assessed a nationwide sample of 72,060 middle and high students from the 10th Korea Youth Risk Behavior Web-based Survey (2014). Descriptive analysis, chi-square tests, and multiple logistic regression analysis were used to probe the association between family a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
28
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 28 publications
12
28
0
4
Order By: Relevance
“…The main related factors include having friends who are addicted, being offered cigarettes, and ease of access [40]. However, relatives and accomplices who smoke played an important role in in uencing these practices [16], consistent with a study that reported a signi cant association between the status of family and friends and adolescent behavior [41].…”
Section: Discussionsupporting
confidence: 68%
“…The main related factors include having friends who are addicted, being offered cigarettes, and ease of access [40]. However, relatives and accomplices who smoke played an important role in in uencing these practices [16], consistent with a study that reported a signi cant association between the status of family and friends and adolescent behavior [41].…”
Section: Discussionsupporting
confidence: 68%
“…The main related factors include having friends who are addicted, being offered cigarettes, and ease of access [39]. However, relatives and accomplices who smoke played an important role in influencing these practices [16], consistent with a study that reported a significant association between the status of family and friends and adolescent behavior [40]. Therefore, teenagers in Aceh and the world at large are highly influenced by their associates, and hence, they tend to adopt common behaviors [41].…”
Section: Discussionsupporting
confidence: 66%
“…It was also stated that the main related factors include having friends who are addicted, being offered cigarettes, and ease of access [39]. However, relatives and accomplices who smoke played an important role in influencing these practices [16], consistent with a study that reported a significant association between the status of family and friends and adolescent behavior [40]. Therefore, teenagers in Aceh and the world at large are highly influenced by their associates, and hence, they tend to adopt common behaviors [41].…”
Section: Discussionsupporting
confidence: 52%